Are Huddles the Missing PEACE of the Puzzle in Implementing Clinical Innovation for the Eating Disorder and Autism Comorbidity? - Smith, Katherine Amanda; Tchanturia, Kate (Frontiers in Psychiatry, 2020)
Huddles are brief, time-limited, focused meetings to help organise and support clinical teams. Huddles have demonstrated their value and transferable benefits across a range of settings. Based on their transferable nature, their potential could be unacknowledged as a clinical implementation technique, particularly in specific subgroups of patients with anorexia who need a higher level of care. An innovative clinical pathway aimed at supporting autistic patients with eating disorders (PEACE Pathway) evaluated the use of weekly PEACE huddles for the multidisciplinary team as part of the implementation process across a 12-month period. A total of 283 responses evaluated the huddle as useful on average 84/100. Using content analysis, several perceived benefits were found of the huddles which were in line with the underpinnings of traditional huddles, suggesting that huddles are transferable as implementation techniques, as evidence by a team providing higher-level care for eating disorders.